Relationship of Service care-receiving Quality and A1C level of Patients with Type 2 Diabetes Mellitus in Bangkok Metrop - Daengbua, Pornpan; Koshakri, Rukchanok; Rerkluenrit, Juntima (Journal of The Royal Thai Army Nurses, 2023)
This descriptive correlation study was conducted for the purpose of describing the quality of diabetes care receiving in term of health promotion, prevention of complications, and continuity of care with A1C level of patients with type 2 diabetes mellitus in 12 community included 185 patients and treated in a public health center in the Bangkok Metropolitan. This research using the concept of quality of care by Donabedian. The data were collected between February to March 2021, using the questionnaire included two-part questionnaire included general information and the diabetes care receiving. The data were analyzed using Spearman Rank correlation coefficient. The results showed that the participants had A1C level between 5.60% - 13.80%, 35.7% of participants can control A1C level well (A1C < 7%). The results of the correlation analysis revealed that a significant moderated negative correlation with diabetes care receiving in term of health promotion and continuity of care (r = -.352 and -.346, p < .01) and a significant low negative correlation with diabetes care receiving in term of prevention of complications (r = -.210, p < .01). The results of the study could be planned basic information management diabetes care practice guideline development in the future.